Ensuring Safety in Construction by Application of Visual and Measuring Control - Petrovich, Ivanov Victor; Nikolaevich, Delendik Mikhail; Stanislavovich, Sarsky Andrei; Grigorievich, Gorbash Vladimir; Ivanovich, Klevzovich Viktor (European Journal of Life Safety and Stability (2660-9630), 2022)
The article considers the basic requirements for visual-measuring control during the construction of buildings and structures. The regulatory documents regulating this type of non-destructive testing are indicated. The devices and optical devices used in the process of performing visual-measuring control are described